Validity and Reproducibility of the 3D VECTRA Photogrammetric Surface Imaging System for the Maxillofacial Anthropometric Measurement on Cleft Patients - Saffai, Lyddia; Othman, Siti Adibah; Wan Hassan, Wan Nurazreena (2019)
Objectives To validate the accuracy and reproducibility of linear measurements of three-dimensional (3D) images and to compare the measurements with direct anthropometry method on cleft lip and palate (CLP) patients. Materials and Methods Twenty-six linear facial measurements were derived from 25 standardized surface landmarks obtained from 37 cleft patients (mean age 23.84 years, standard deviation ±6.02). They were taken manually with calipers and compared it with the digitally calculated distance on the 3D images captured using VECTRA M5-360̊ Imaging System with pre-marked landmarks. Another pair of 26 linear measurements were computed on the 3D images 2 weeks apart for intra- and inter-observer agreements. Statistical analyses used were paired t–test, the Bland-Altman analysis and the intra-class correlation coefficient index (ICC). Results Generally most of the linear measurements have no statistically significant difference between proposed method and direct anthropometry linear measurements. Nevertheless, bias of the 3D imaging system presents in the linear measurements of the nose width, and the upper vermillion height. The measurements’ mean biases were within 2 mm but the 95% limits of agreement were more than 2mm. Intra- and inter-observer measurements generally showed good reproducibility. Four inter-observer measurements, the upper and lower face heights, nose width and pronasale to left alar base were just slightly clinically significance. Conclusions Measurements obtained from this 3D imaging system is valid and reproducible for evaluating CLP patient. Clinical relevance The system is suitable to be used in clinical setting for cleft patients. However, training of the operator is strictly advisable.